Atividades Didáticas para Ensino de Português em Ambiente Digital: uma análise semiótica - Daniervelin Renata Marques Pereira (2010)
In this work, we have dedicated to an information survey that is summarized in a speech about the making and the speech of the making, produced by thirteen teachers of introductory courses of Portuguese through distance education in universities. It was used: 1) aquestionnaire that focused on the practice of distance education, emphasizing the development of educational activities and a comparison between both face-to-face and distance designs; 2) activities that guided the practice of teachers and 3) the interaction during a one-term on-line course. Based on the French semiotics, we analyzed data in search ofinformation about the production of meaning in the text, in other words, what was behind the teachers speech. According to the premise of this theory, we deal here with the marks of enunciation and the meaning effects created in the text, so we eliminated the term "practice"and used " the saying of the making", since our theoretical construct provides that practice as a text. In these texts (the questionnaire responses, the directions of activities and the on-line interaction), we tried to capture the logical narrative structure in the path of the subjectsenrolled and how was their development, especially concerning the teacher as an subject, in relation to other subjects and with the objects as well as his/her modal existence. The enunciation categories (person, time and space), the argumentative procedures and thematictrails with his figurative revetment helped us to understand the specificities of the context portrayed by the teachers. In the search of similarities and differences, we compared the courses of themes and figures in order to verify the relationship established between them.The results show that the differences appear when comparing the discourses among the teachers and these discourses with the critical discourse. Similarities among education topics such as language conception, the course objectives and references matched in a large amount, while others varied more about the uniformity or distinction between education designs. Examples: teaching activities and methodology. We cite here at least three of the most common occurrences: 1) it is argued in favor of the identity of these aspects for courses that have the same pedagogical approach, 2) it is assumed the use of the same elements to courses that occur in different environments, although there is a recognition that this should not bedone and 3) advocacy of a foray inclusion into new practices always adapted to the new environment. Concepts that are reflected in these discourses not only link to the teacher's voice, but also to the school and, ultimately, to society itself.